2017
DOI: 10.1055/s-0043-118910
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Zinc Alpha2 Glycoprotein on Lipid Metabolism of Liver in High-Fat Diet-Induced Obese Mice

Abstract: Zinc alpha2 glycoprotein (ZAG) is a new type of adipokine involved in adipose tissue mobilization, however, little is known about its lipid metabolism effect in liver. Therefore, we investigated the effects of ZAG in the regulation of hepatic lipid accumulation. Mice were randomly divided into two groups; one was fed a normal diet and another was fed a high-fat diet for eight weeks to establish obesity model. After that, the normal diet group was divided into ND (injection of pcDNA3.1) and NDZ (injection of ZA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
2
11
0
Order By: Relevance
“…S4b ). Zinc alpha 2-glycoprotein (Azgp1) is a lipid mobilizing factor 24 , and its expressions were significantly higher in KKAy + Dapa than KK or KKAy (Supplementary Fig. S4c ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S4b ). Zinc alpha 2-glycoprotein (Azgp1) is a lipid mobilizing factor 24 , and its expressions were significantly higher in KKAy + Dapa than KK or KKAy (Supplementary Fig. S4c ).…”
Section: Resultsmentioning
confidence: 99%
“…The second is the effect of lipid mobilizing factor, Azgp1 (zinc alpha 2-glycoprotein). Injection of Azgp1 expression plasmid reduces hepatic TG content and expressions of lipogenic genes 24 . In the current study, expressions of Azgp1 were significantly elevated in liver of KKAy + Dapa compared with KKAy.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the issue of endogenous vs. exogenous ZAG, our previous studies together with others showed that injection of a ZAG expression plasmid in mice could increase serum ZAG levels (Gong et al, 2009 ; Fan et al, 2017 ) as well as Zag gene expression in eVAT (Gong et al, 2009 ). In our present study, we found that administration of a ZAG expression plasmid to mice led to an increase in Zag expression in pVAT (Figure 5A ) as well as a tendency toward an increase in sWAT (Figure 4B ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, dysfunction of zinc signaling may be involved in the pathogenesis of diabetes mellitus (Nicolson et al 2009). On the other hand, zinc supplementation protected against apoptosis and reduced liver damage in patients with chronic hepatitis C or compensated cirrhosis (Fan et al 2017;Matsuoka et al 2009;Sun et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These are essential amino acids, which participate in the regulation of body protein balance and insulin secretion, modulation of the immune system, and reduction of muscle injury post-exercise (Fan et al 2017;Holecek 2018). Elevated blood levels of BCAA are found in obesity and type 2 diabetes mellitus (Batch et al 2014;Newgard et al 2009), making them putative biomarkers of these metabolic diseases (Siomkajlo et al 2017).…”
Section: Introductionmentioning
confidence: 99%